PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS PERUSAHAAN CONSUMER GOODS DIMODERASI PROFITABILITAS - Devi, Heidy Paramitha; Ningrum, Berlian Kusuma; Supatminingsih, Sri (JURNAL ILMIAH EDUNOMIKA, 2022)
This study aims to determine the effect of Good Corporate Governance on Financial Distress with Financial Performance as a Moderating Variable. This research was conducted on Consumer Goods companies listed on the IDX for the 2018-2019 period. This study uses quantitative research methods. The population in this study were 52 companies. The sampling method used purposive sampling method and the resulting sample of 44 companies with a period of 3 years so that a sample of 132 company data was obtained. However, there are outlier data, so 106 research data are obtained. The research analysis uses Multiple Linear Regression and Moderate Regression Analysis (MRA) using SPSS version 25 software. The results show that (1) the Board of Commissioners has an effect on Financial Distress (2) the Board of Directors has no effect on Financial Distress (3) the Audit Committee has no influence on Financial Distress (4) The Board of Commissioners has no effect on Financial Distress which is moderated by Profitability (5) The Board of Directors has an effect on Financial Distress which is moderated by Profitability (6) The Audit Committee has an effect on Financial Distress which is moderated by Profitability. Keywords : Good Corporate Governance, Financial Distress, Financial Performance, Consumer Goods companies